2020
DOI: 10.3892/ijmm.2020.4592
|View full text |Cite
|
Sign up to set email alerts
|

The JAK2/STAT3 pathway inhibitor, AG490, suppresses the abnormal behavior of keloid fibroblasts in vitro

Abstract: AG490 is a selective inhibitor of the Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) signaling pathway. The present study examined its effects on the abnormal behavior of human keloid fibroblasts (HKFs) and evaluated its potential use in the treatment of keloids. Human normal fibroblasts (HNFs) and HKFs were treated with increasing concentrations of AG490. The proliferation of HNFs and HKFs was inhibited by AG490 in both a time-and concentration-dependent manner by increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…Consistent with prior reports identifying the activity and accessibility of STAT3 as central in the hyper-proliferative/hyper-motile phenotype of keloid cells [5] and similar to our prior findings [14], fibroblasts from patients with STAT3 LOF showed reduced closure in the scratch assay ( Fig 1D). Keloid STAT3-mediated phenotypes in keloid cells are also known to be influenced by co-transcription with JAK2 [10]. Consistent with these reports, the accelerated wound closure in the keloid cell line was blocked by the JAK1/2 inhibitor ruxolitinib ( Fig 1D) while also inhibiting closure time in the HV fibroblast line in a dose-dependent manner (Fig 1E and 1F).…”
Section: Modeled Wound Closure In a Keloid Fibroblast Cell Line Was Dsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with prior reports identifying the activity and accessibility of STAT3 as central in the hyper-proliferative/hyper-motile phenotype of keloid cells [5] and similar to our prior findings [14], fibroblasts from patients with STAT3 LOF showed reduced closure in the scratch assay ( Fig 1D). Keloid STAT3-mediated phenotypes in keloid cells are also known to be influenced by co-transcription with JAK2 [10]. Consistent with these reports, the accelerated wound closure in the keloid cell line was blocked by the JAK1/2 inhibitor ruxolitinib ( Fig 1D) while also inhibiting closure time in the HV fibroblast line in a dose-dependent manner (Fig 1E and 1F).…”
Section: Modeled Wound Closure In a Keloid Fibroblast Cell Line Was Dsupporting
confidence: 83%
“…First described in neoplastic cells by Dr. Otto H. Warburg [8], the Nobel winning discovery identified the propensity for rapidly dividing cells to preferentially utilize glycolysis for ATP generation at the expense of oxidative phosphorylation (OxPhos) despite available oxygen [9]. Subsequent research identified over activity of signal transducer and activator of transcription 3 (STAT3; in conjunction with JAK2 [10]) as a central mediator of keloid pathology [5,11]. Furthermore, recent publications in cancer cells have identified the JAK/ STAT signaling pathways as an inducer of Warburg metabolism [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently examined a few Th2 markers in keloids (20), while another study found increases for the IL-17/IL-22-induced products, S100A7 and hBD2 (53). Additionally, dysregulation of the IL-17/IL-6 axis (11) and/or JAK/STAT-signaling (54,55) have also been investigated. The present study expands on prior investigations and provides a comprehensive molecular profiling of keloids, identifying a significant immune component in both lesional and non-lesional skin, as well as linking keloids with fibrosis and cartilage/bone-differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…AD, psoriasis, alopecia areata) (81), modulating a range of immune responses, including the Th2 (IL-4, IL-13, CCL18), Th1 (IFNg), and Th17/Th22 (CCL20, S100As) pathways (82). Preliminary studies evaluating inhibition of JAK/STAT signaling in human keloid fibroblasts (54,55), and in a humanized keloid animal model (83), have demonstrated promising results. There are several JAK inhibitors in clinical development showing efficacy for various dermatologic disorders (81,82,84) and could be a therapeutic strategy worth investigating in keloids.…”
Section: Discussionmentioning
confidence: 99%
“…However, VEGF‐A has been implicated in the formation of adhesions after intra‐abdominal, pericardial or pleural interventions 3,9,17‐19 . Dysregulation of angiogenesis and overexpression of VEGF has been identified in the pathogenesis of overt fibrosis in several conditions, including the formation of keloid in wounds, tendon healing, and bleomycin‐induced pulmonary fibrosis 20‐26 . Potential mechanisms include the increase in vascular permeability, extravasation, and deposition of fibrinogen and cellular migration 3 …”
Section: Introductionmentioning
confidence: 99%